Royal motifs in the Pentateuchal portrayal of Moses - Mathews, Danny (Library of Hebrew Bible/Old Testament studies ;, 2012)
Moses is portrayed through the use of royal motifs, such as his abandonment at birth, flight from Pharaoh, portrayal as a shepherd, as a semi-divine figure, temple builder, military general, and lawgiver. These well-known motifs that have been typically used to depict four famous rulers in the ancient Near East, Hammurabi, Esarhaddon, Nabonidus, and Cyrus, have been adapted by the authors of the Pentateuch to affirm Moses as a more ancient leader, whose work has resulted in the constitution of the community of Israel. As a result, Israel''s identity and enduring existence rest upon the authori.